MEMAHAMI KONSEP DAN ORIENTASI PERKEMBANGAN SUMBER DAYA MANUSIA PADA MADRASAH DAN PESANTREN - Siti Maghfiroh; Saiful Hadi (STKIP Pesisir Selatan, 2026)
The dynamics of modernization compel madrasahs and pesantren to revitalize their Human Resource (HR) management orientation to maintain institutional competitiveness without uprooting their religious traditions. Historically, previous studies on HR within Islamic educational institutions have predominantly emphasized conventional personnel administration and singular charismatic leadership. This tendency leaves a significant literature gap (research gap) regarding how these institutions strategically adapt to contemporary talent management demands in the Society 5.0 era. Responding to this void, the novelty of this study lies in constructing a theoretical framework that integrates Islamic work ethics with modern Agile Human Resources instruments. Employing a qualitative methodology through a Systematic Literature Review (SLR) approach and critical analysis of educational policies over the past decade, this study dissects this paradigm shift. The findings indicate that the current trajectory of HR development necessitates a transition from traditional devotion-based models toward strengthening hybrid competencies, encompassing digital literacy, transformative leadership, and structured performance appraisal systems. This transformation critically depends on the leadership's capability to formulate an inclusive succession scheme rooted in Maqashid Sharia.